Lumbar Intervertebral Disc Herniation Masquerading as an Epidural Hematoma: A Case Report and Review of the Literature. Issue 3 (July 2018) - Jain, Nikhil; Crouser, Nisha; Yu, Elizabeth
Abstract : Case: A 50-year-old man developed acute back and bilateral leg pain after minor trauma. Laboratory tests and routine radiographs were unremarkable. Magnetic resonance imaging (MRI) showed a 5 × 15 × 42-mm longitudinally oriented mass behind the L2-L3 interspace that obliterated the subarachnoid space and displaced the nerve roots. The mass was isointense on T1-weighted imaging and showed mixed low and high signals on T2-weighted imaging. Based on the clinical history and the imaging findings, a provisional diagnosis of spinal epidural hematoma (SEH) was made. A laminectomy was performed at L2-L3; intraoperatively, a large disc herniation was found at L2-L3, with no evidence of hematoma. Conclusion: MRI findings of SEH and disc herniation have been well described in the literature. To our knowledge, this is the third report of intraoperatively confirmed disc herniation with MRI findings suggestive of SEH These discordant MRI and intraoperative findings illustrate that an SEH and a disc herniation may not always be distinguishable on MRI and may require surgical confirmation.